2015
DOI: 10.1080/00032719.2014.999272
|View full text |Cite
|
Sign up to set email alerts
|

Simple and Rapid Quantification of Folic Acid in Pharmaceutical Tablets using a Cathodically Pretreated Highly Boron-doped Polycrystalline Diamond Electrode

Abstract: A simple, rapid, and sensitive electroanalytical method for the direct quantification of folic acid was developed using square-wave voltammetry with a cathodically pretreated highly borondoped polycrystalline diamond electrode. The morphology and structure of this electrode were Downloaded by [University of Lethbridge] at 03:15 05 October 2015 2investigated by scanning electron microscopy and Raman spectroscopy. The electrochemical behavior of folic acid was studied by cyclic voltammetry and an irreversible ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…2), indicating the diffusion-controlled nature of the electrode process. The linear dependence obeys the following equation (1): The optimization of SWV parameters influencing the current response of analyte is an important step in the development of electroanalytical methodology (Cinková et al, 2015b). For this purpose, instrumental parameters such as amplitude (in the range of 10-150 mV) and frequency (in the range of 10-150 Hz) were optimized using 1 × 10 -4 mol·L -1 nicotine in PB (pH 9).…”
Section: Resultsmentioning
confidence: 99%
“…2), indicating the diffusion-controlled nature of the electrode process. The linear dependence obeys the following equation (1): The optimization of SWV parameters influencing the current response of analyte is an important step in the development of electroanalytical methodology (Cinková et al, 2015b). For this purpose, instrumental parameters such as amplitude (in the range of 10-150 mV) and frequency (in the range of 10-150 Hz) were optimized using 1 × 10 -4 mol·L -1 nicotine in PB (pH 9).…”
Section: Resultsmentioning
confidence: 99%
“…In this point of view, electrochemical techniques become good candidates for this task. Researchers working in this are reported that modification of working electrodes are needed in order to overcome slow kinetics with a need of high reduction potentials of oxidation procedure of FA . Also, it has been found that two steps (adsorption and stripping) contained electroanalytical techniques like stripping voltammetry provide effective determination of FA .…”
Section: Resultsmentioning
confidence: 99%
“…In this aspect, electrohemical sensors can be accepted as good candidates for this task . Since the direct electrochemical oxidation of FA on most of the conventional electrode materials demonstrates slow kinetics with a need of high reduction potentials , many efforts have been devoted to develop more effective electrodes for FA detection .…”
Section: Introductionmentioning
confidence: 99%
“…Folic acid is another example of a vitamin belonging to the B complex, it is an essential vitamin and soluble in water, has great importance for human health especially in the period of rapid cell division and growth. CV and SWV were employed as analytical techniques in the development of methodology using a BDD electrode, anodically pretreated at 2.5 V in 1 mol L −1 H 2 SO 4 for 30 s to clean its surface followed by cathodic pretreatment by applying −2.5 V for 60 s to obtain a predominantly hydrogen‐terminated surface on the working electrode . The analytical curve was linear in the SWV concentration range from 1×10 −7 to 1.7×10 −4 mol L −1 with the value of the detection limit of 3.0×10 −8 mol L −1 .The practical applicability of the method was successfully demonstrated for the analysis of pharmaceutical tablets with satisfactory recoveries (from 100 to 104 %).…”
Section: Electroanalysis Of Pharmaceuticalsmentioning
confidence: 99%